Poly(butylene succinate-co-ε-caprolactone) Copolyesters: Enzymatic Synthesis in Bulk and Thermal Properties - María Núñez; Sebastián Muñoz-Guerra; Antxon Martínez de Ilarduya (Polymers, 2021)
This work explores for the first time the enzymatic synthesis of poly(butylene-co-ε-caprolactone) (PBSCL) copolyesters in bulk using commercially available monomers (dimethyl succinate (DMS), 1,4-butanediol (BD), and ε-caprolactone (CL)). A preliminary kinetic study was carried out which demonstrated the higher reactivity of DMS over CL in the condensation/ring opening polymerization reaction, catalyzed by Candida antarctica lipase B. PBSCL copolyesters were obtained with high molecular weights and a random microstructure, as determined by 13C NMR. They were thermally stable up to 300 °C, with thermal stability increasing with the content of CL in the copolyester. All of them were semicrystalline, with melting temperatures and enthalpies decreasing up to the eutectic point observed at intermediate compositions, and glass transition temperatures decreasing with the content of CL in the copolyester. The use of CALB provided copolyesters free from toxic metallic catalyst, which is very useful if the polymer is intended to be used for biomedical applications.